SENGKETA HASIL PEMILIHAN PRESIDEN 2024 DI MAHKAMAH KONSITUSI: ANALISIS FRAMING PEMBERITAAN MEDIA LOKAL JAWA TENGAH SUARA MERDEKA DAN SOLOPOS - Trilestari, Linda; Nurfaizi, Kevin Rohman; Kurniawan, Dani; Muntaha, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The study investigates how Solo Post and Voice Merdeka, two local media outlets, interpret and discredit the 2024 presidential election outcome. They used Robert N. Entman’s framing concept. In Indonesia, the presidential election has raised a lot of controversy, especially with regard to the Constitutional Court’s decision on the election results. The purpose of framing analysis is to study how the media frames publicly received communications and how it affects people’s perceptions of justice and integrity during the democratic process. The results showed that Merdeka’s voice remained neutral, and Solo Post was more likely to broadcast news with a positive or supportive perspective on the 02. The study provides an excellent understanding of the role of the media in the political and legal context in Indonesia and emphasizes the importance of framing analysis to understand how the media shapes public understanding of social reality